Meaning salience as a moderator of the relationship between presence of meaning in life and wellness - Thomas A. Jude; Kaitlyn M. Vagnini; Kevin S. Masters; Stephanie A. Hooker (Discover Psychology, 2024)
Abstract Meaning salience, or awareness of meaning in the present moment, is an emerging concept with potential implications for health and wellness. The purpose of this study was to understand the relationships between meaning salience and eight dimensions of wellness, and to see whether meaning salience moderated the relationship between presence of meaning and wellness. Participants (N = 1711) were recruited to complete a cross-sectional survey through Amazon’s Mechanical Turk. Meaning salience was related to better wellness in seven of the eight wellness domains (healthy eating and activity, financial stress, occupational wellness, sleep, perceived wellness, social wellness, and stress, excluding avoiding unhealthy foods). Meaning salience significantly moderated the relationships between presence of meaning and four of eight wellness dimensions, such that at high levels of meaning salience, both high and low presence of meaning had stronger relationships with wellness. Those with high meaning salience and high presence of meaning scored best on four wellness dimensions; however, those with high meaning salience and low presence of meaning scored the worst on four wellness dimensions. Future research should explore what factors drive the relationship between meaning salience and wellness.